Unraveling the Complexity of the Jevons Paradox: The Link Between Innovation, Efficiency, and Sustainability - Giampietro, Mario; Mayumi, Kozo (Frontiers in Energy Research, 2018)
The term ‘Jevons Paradox’ flags the need to consider the different hierarchical scales at which a system under analysis changes its identity in response to an innovation. Accordingly, an analysis of the implications of the Jevons Paradox must abandon the realm of reductionism and deal with the complexity inherent in the issue of sustainability: When studying evolution and real change how can we define “what has to be sustained” in a system that continuously becomes something else? In an attempt to address this question this paper presents three theoretical concepts foreign to conventional scientific analysis: (i) complex adaptive systems—to address the peculiar characteristics of learning and self-producing systems; (ii) holons and holarchy—to explain the implications of the ambiguity found when observing the relation between functional and structural elements across different scales (steady-state versus evolution); and (iii) Holling’s adaptive cycle—to illustrate the existence of different phases in the evolutionary trajectory of a complex adaptive system interacting with its context in which either external or internal constraints can become limiting. These concepts are used to explain systemic drivers of the Jevons Paradox. Looking at society’s thermodynamic foundations, sustainability is based on a dynamic balance of two contrasting principles regulating the evolution of complex adaptive systems: the minimum entropy production and the maximum energy flux. The co-existence of these two principles explains why in different situations innovation has to play a different role in the ‘sustainable development’ of society: (i) when society is not subject to external biophysical constraints improvements in efficiency serve to increase the final consumption of society and expand its diversity of functions and structures; (ii) when the expansion of society is limited by external constraints improvements in efficiency should be used to avoid as much as possible the loss of the existing diversity. It is concluded that sustainability cannot be achieved by technological innovations alone, but requires a continuous process of institutional and behavioral adjustment.